Memorandum of cooperation between Universiti Teknologi MARA and Nicolaus Copernicus University in Torun, Poland / Fakulti Perubatan - Universiti Teknologi MARA, Fakulti Perubatan (Universiti Teknologi MARA (UiTM), 2021)
UiTM and Nicolaus Copernicus University in Torun will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.